2019
DOI: 10.1002/jcb.29248
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of NBR1 in urothelial carcinoma cells enhances rapamycin‐induced apoptosis through impaired autophagy and mitochondrial dysfunction

Abstract: Rapamycin is well‐recognized in the clinical therapeutic intervention for patients with cancer by specifically targeting mammalian target of rapamycin (mTOR) kinase. Rapamycin regulates general autophagy to clear damaged cells. Previously, we identified increased expression of messenger RNA levels of NBR1 (the neighbor of BRCA1 gene; autophagy cargo receptor) in human urothelial cancer (URCa) cells, which were not exhibited in response to rapamycin treatment for cell growth inhibition. Autophagy plays an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Finally, we identified all of those three miRNAs were GIN-related miRNAs. As showed in Figure 2A and 2B , let-7b-3p was positive co-expression with BCL2 (R = 0.327, P < 0.001) and NBR1 (R = 0.318, P < 0.001), among which the BCL2 was reported to inhibit autophagy [ 14 , 15 ], while NBR1 was reported to promote autophagy [ 16 , 17 ]. miR-26a-5p and HSP-A8 were negative co-expression (R = −0.329, P < 0.0001), which was an autophagy inhibitor [ 18 ]; miR-151a-5p and GRID1 (R = −0.291, P < 0.0001) and FOXO1 (R = −0.291, p < 0.0001) were negative co-expression, amongst which FOXO1 was reported as an autophagy promotor [ 19 ]; while miR-151a-5p was positive co-expression with RHEB (R = 0.358, p < 0.0001), BIRC5 (R = 0.316, p < 0.0001) and HSP90AB1 (R = 0.391, p < 0.0001), among which RHEB was reported as an autophagy promotor [ 20 ], while BIRC5 and HSP90AB1 were reported as autophagy inhibitor [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we identified all of those three miRNAs were GIN-related miRNAs. As showed in Figure 2A and 2B , let-7b-3p was positive co-expression with BCL2 (R = 0.327, P < 0.001) and NBR1 (R = 0.318, P < 0.001), among which the BCL2 was reported to inhibit autophagy [ 14 , 15 ], while NBR1 was reported to promote autophagy [ 16 , 17 ]. miR-26a-5p and HSP-A8 were negative co-expression (R = −0.329, P < 0.0001), which was an autophagy inhibitor [ 18 ]; miR-151a-5p and GRID1 (R = −0.291, P < 0.0001) and FOXO1 (R = −0.291, p < 0.0001) were negative co-expression, amongst which FOXO1 was reported as an autophagy promotor [ 19 ]; while miR-151a-5p was positive co-expression with RHEB (R = 0.358, p < 0.0001), BIRC5 (R = 0.316, p < 0.0001) and HSP90AB1 (R = 0.391, p < 0.0001), among which RHEB was reported as an autophagy promotor [ 20 ], while BIRC5 and HSP90AB1 were reported as autophagy inhibitor [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…32 AMPKa also stimulates autophagy by inhibiting mTOR kinase. 32,33 Low AMPKa phosphorylation is also seen in bladder cancer. 34 AKT activates mTOR by phosphorylating it, and then activated mTOR suppresses autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. 46 stated that the deterioration in NRB1 functioning restrained autophagosome formation and disrupted the level of p62 protein and autophagosome turnover. They reported that rapamycin activated protective autophagy by increasing the amount of NRB1 in bladder cancer cell lines.…”
Section: Survival Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 99%